Characterization of microsatellite markers for pinedrops, Pterospora andromedea (Ericaceae), from Illumina MiSeq sequencing1. (29th October 2014) - Grubisha, Lisa C.; Nelson, Bailey A.; Dowie, Nicholas J.; Miller, Steven L.; Klooster, Matthew R.
Abstract : Premise of the study: Pterospora andromedea (Ericaceae) is a mycoheterotrophic plant endemic to North America with a disjunct distribution. Eastern populations are in decline compared to western populations. Microsatellite loci will allow comparison of genetic diversity in endangered to nonthreatened populations. Methods and Results: Illumina MiSeq sequencing resulted in development of 12 polymorphic microsatellite loci from 63 perfect microsatellite loci tested. One polymorphic locus was obtained from a traditional enrichment method. These 13 loci were screened across two western and two eastern populations. For western and eastern populations, respectively, number of alleles ranged from one to 10 and one to four, and observed heterozygosity ranged from 0.000 to 0.389 and 0.000 to 0.143. Conclusions: These are the first microsatellite loci developed for Pterospora . They will be useful in conservation efforts of the eastern populations and for examination of population genetic parameters at different geographic scales and comparison with mycorrhizal fungal hosts.